Reservoirs of Sri Lanka and their fisheries . - "Silva, Sena S . de" (Rome, 1988)
Sri Lanka, a continental trpoical island of 65,000 km12, is reputed for its ancient irrigation reservoirs, constructed over the last 2000 years. The island, which is devoid of natural lakes has 3 ha of artificially created lentic waters for every km2. These reservoirs are mostly confined to the dry zone which receives less than 187 cm of rainfall per annum.
Keywords: Food & Agriculture organization of the United Nations .